TLR signaling in mast cells: common and unique features - Sandig, Hilary; Bulfone-Paus, Silvia (Frontiers in Immunology, 2012)
In addition to the well known role of mast cells in immunity to multi-cellular parasites and in the pathogenesis of allergy and asthma, the importance of mast cells in the immune defense against bacteria and viruses is increasingly being recognized. Their location in the skin, gut and airways puts mast cells in an ideal location to encounter and respond to pathogens, and in order to perform this function, these cells express a variety of pattern recognition receptors (PRRs), including Toll-like receptors (TLRs). Mast cells respond to TLR ligands by secreting cytokines, chemokines and lipid mediators, and some studies have found that TLR ligands can also cause degranulation, although this finding is contentious. In addition, stimulation via TLR ligands can synergize with signaling via the FcεR1, potentially enhancing the response of the cells to antigen in vivo. A great deal is now known about TLR signaling pathways. Some features of these pathways are cell type specific, however, and work is under way to fully elucidate the TLR signaling cascades in the mast cell. Already, some interesting differences have been identified. This review aims to address what is known about the responses of mast cells to TLR ligands and the signaling pathways involved. Given the location of mast cells at sites exposed to the environment, the response of these cells to TLR ligands must be carefully regulated. The known mechanisms behind this regulation are also reviewed here.